The dark sunrise - McCauley, Terrence (McCauley, Terrence. Sheriff Aaron Mackey western., 2020)
"At long last, U.S. Marshal Aaron Mackey and Deputy Billy Sunday will see crime baron James Grant and his kill-crazy cronies stand trial for the mayhem and suffering they unleashed on the people of Dover Station. But as Montana Territory's statehood is approaching, murdering devils like Grant can no longer be tolerated in positions of political power. Or can they? Montana's capital of Helena follows its own set of laws--laws that not only set Grant free, but give peacekeeping authority to a sadistic murdering gunslinger like Colonel Warren Bell, Mackey's commanding officer during the war. The city's leaders prefer keeping killers like Grant and Bell under their thumbs. Mackey knows there's no controlling these bloodthirsty madmen. And if they think they're above the law, then Mackey and Billy will just have to appoint themselves judge, jury, and executioners..."--